On violence : Arendtian reflections - Dallmayr, Fred (Journal of power and ethics, 2001)
We live in a world of steadily escalating violence-from ethnic cleansings and genocides to seemingly unending "terror wars." Some thirty years ago, Hannah Arendt wrote her reflections "on Violence" which drew a sharp line between politics and political power, on the one hand, and violence and destruction, on the other. The present essay explores the continued relevance of her argument in our time, proceeding in three steps. The opening section offers a close reading of Arendt's reflections and their place in her larger opus. Continuing the line of authors criticized by Arendt, the middle section reviews some recent literature which, in center staging violence, blurs the distinction between violence and politics. The conclusion reaffirms Arendt's distinction while simultaneously revising her conception through some borrowings from Gandhi and the tradition of public ethics. [PUBLICATION ABSTRACT]